BH4 domain peptides derived from Bcl-2/Bcl-XL as novel tools against acute pancreatitis - Vervliet, Tim (Cell Death Discov, 2018)
Biliary acute pancreatitis (AP) is a serious condition, which currently has no specific treatment. Taurolithocholic acid 3-sulfate (TLC-S) is one of the most potent bile acids causing cytosolic Ca(2+) overload in pancreatic acinar cells (PACs), which results in premature activation of digestive enzymes and necrosis, hallmarks of AP. The inositol 1,4,5-trisphosphate receptor (IP(3)R) and the ryanodine receptor (RyR) play major roles in intracellular Ca(2+) signaling. Inhibition of these endoplasmic reticulum-located channels suppresses TLC-S-induced Ca(2+) release and necrosis, decreasing the severity of AP. Anti-apoptotic B-cell lymphoma (Bcl)-2-family members, such as Bcl-2 and Bcl-X(L), have emerged as important modulators of IP(3)Rs and RyRs. These proteins contain four Bcl-2 homology (BH) domains of which the N-terminal BH4 domain exerts critical roles in regulating intracellular Ca(2+) release channels. The BH4 domain of Bcl-2, but not of Bcl-X(L), binds to and inhibits IP(3)Rs, whereas both BH4 domains inhibit RyRs. Although clear cytoprotective effects have been reported for these BH4 domains, it remains unclear whether they are capable of inhibiting pathological Ca(2+)-overload, associated with AP. Here we demonstrate in PACs that the BH4 domains of Bcl-2 and Bcl-X(L) inhibit RyR activity in response to the physiological agonist cholecystokinin. In addition, these BH4 domains inhibit pathophysiological TLC-S-induced Ca(2+) overload in PACs via RyR inhibition, which in turn protects these cells from TLC-S-induced necrosis. This study shows for the first time the therapeutic potential of BH4 domain function by inhibiting pathological RyR-mediated Ca(2+) release and necrosis, events that trigger AP.